Living Materials: Preserving Student Innovation in Art and Science through Digital Twins and AI in Partnership with Qatar National Library : What Happens To Your Work After You Graduate? - Arif Shaon (13761784) (2026)
Presentation was part of the Karak Hour Workshop at the Virginia Commonwealth University School of the Arts in Qatar (VCUarts), Doha (Qatar) – 14th of January 2026. This presentation documents a Manara – Qatar Research Repository a Qatar National Library outreach and training session delivered to Virginia Commonwealth University School of the Arts in Qatar (VCUarts) and Hamad Bin Khalifa University (HBKU) students as part of the Living Materials : Preserving Student Innovation in Art and Science Through Digital Twins and AI in Partnership with Qatar National Library, funded under the Qatar Research, Development, and Innovation Council (QRDI) Multiversity Grants Programme (2025-2026). The session addresses a critical but often overlooked question facing graduating students: what happens to creative and research work after graduation? Drawing on real-world examples from art, design, and engineering education, the presentation explores how student projects – particularly material-based, practice-led, and process-driven work are frequently lost due to physical disposal, fragile storage practices, platform dependency, and digital obsolescence. The presentation introduces key concepts in long-term digital curation, including the value of preserving process data alongside final outputs, the limitations of commercial cloud storage, and the role of trusted research repositories in ensuring long-term access, attribution, and reuse. It highlights Manara – Qatar Research Repository, as a platform that enables students to publish creative and research outputs with persistent identifiers (DOIs), appropriate licensing, and active digital preservation supported by Qatar National Library. Through practical guidance on file organisation, copyright and licensing, discoverability, and research visibility, the session demonstrates how students can take control of their digital legacy, enhance employability, and contribute to Qatar’s national knowledge infrastructure. The presentation also situates student work within a broader global research ecosystem, emphasizing citability, verification, and long-term impact in an era increasingly shaped by AI-generated content. This resource is intended for students, educators, librarians, and institutions interested in sustainable models for preserving student innovation, practice-led research, and interdisciplinary creative outputs. Other Information License: http://creativecommons.org/licenses/by/4.0/ See Qatar Research, Development, and Innovation Council (QRDI-C) – Qatar Foundation (QF): Multiversity Grant Project 2025-2026 information on the funder's website: https://www.qf.org.qa/stories/ideas-united-qatar-foundations-multiversity-grants-drive-cross-university